The strength and stiffness of shear webs with and without lightening holes - Kuhn, Paul (National Advisory Committee for Aeronautics, 1942)
Nearly 200 tests were made on the strength of shear webs of 24S-T aluminum alloy, with and without lightening holes. The tests were made in a jig of the single-specimen type, in which the specimen is free to collapse completely without developing diagonal tension. The lightening holes were circular and had either flanged edges or beaded edges, the specimens with flanged edges constituting by far the largest test group.
NACA Wartime Report L-402.
Originally issued as NACA as an Advance Restricted Report (June 1942).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Aluminum alloys.; Holes.; Shear (Mechanics); Strength of materials.; Strains and stresses.; Monocoque construction.; Charts, diagrams, etc.; elektronické knihy; electronic books